Achieving Efficiency with Justice in the Reform of Anti-Corruption Law Enforcement in State-Owned Enterprises - Amir Firmansyah; Suparji; Pujiono Suwandi (Contrarius Indonesia, 2026)
The anti-corruption law enforcement approach in Indonesian State-Owned Enterprises (SOEs) is primarily repressive, necessitating a system that incorporates economic efficiency and legal justice. This situation results in legal uncertainty, the potential criminalization of legitimate business decisions, and low effectiveness in eradicating corruption. The objective of this investigation is to evaluate deficiencies in the anti-corruption law enforcement system in Indonesian SOEs and to develop a model for reconstructing law enforcement that incorporates the principles of efficiency and justice. The research methodology employed is a normative juridical approach, incorporating conceptual, statutory, and comparative approaches. The results suggest that, first, primary weaknesses are the ambiguous boundaries between business risks and corruption, regulatory fragmentation, and the weak integration between prevention and law enforcement mechanisms. Secondly, Singapore's success in eradicating corruption in SOEs is attributed to the strict separation of state and corporate functions through Temasek Holdings, which is bolstered by independent and effective law enforcement by the Corrupt Practices Investigation Bureau. Third, this study suggests an Efficiency-Justice-Based Anti-Corruption Enforcement model that integrates repressive, preventive, and restorative approaches within a coherent legal framework. This model includes the following: the internalization of compliance systems at the corporate level, the increased independence of law enforcement agencies, the harmonization of regulations, the strengthening of the business judgment rule, and the redefining of the concept of state losses.